Aplikasi Herbisida Ramah Lingkungan di Desa Kiusili Kecamatan Bikomi Selatan Kabupaten Timor Tengah Utara - Gebhardus Djugian Gelyaman; Yolanda Getrudis Naisumu; Aloysius Rusae (LPPM Universitas Timor, 2020)
Community service has been carried out in the Nek'amnaut farmer group Kiusili village, Timor Tengah Utara district. The dedication was the use of eco-friendly herbicides made from salt, vinegar, water, and liquid soap. The dedication method was socialization and demonstration of making and spraying of the solution on weeds. Pre-service and post-service questionnaires were filled to find out farmer group knowledge of herbicides in general and the ability made environmentally friendly herbicides. The results showed that an eco-friendly herbicide solution has succeeded in killing weeds. Public knowledge changed from the category of not knowing to be well-informed, marked by an increased in the knowledge score (SP) from 24 to 76. The percentage of the number of farmer group members who well-informed changed from 0 to 83%. The ability category was change from unable to be very capable of making the herbicide, marked by the ability score (SK) increased from 0 to 83. The number of farmer group members who can make the herbicide increased from 0 to 89%. The intensity of the use of synthetic herbicides was decreased in the last three years. Five liters of an environmentally friendly herbicide solution killed weed in 48 m2 area.